2023
DOI: 10.1101/2023.04.07.536063
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Classifier for the Rapid Simultaneous Determination of Sleep-Wake States and Seizures in Mice

Abstract: Independent automated scoring of sleep-wake and seizures have recently been achieved; however, the combined scoring of both states has yet to be reported. Mouse models of epilepsy typically demonstrate an abnormal electroencephalographic (EEG) background with significant variability between mice, making combined scoring a more difficult classification problem for manual and automated scoring. Given the extensive EEG variability between epileptic mice, large group sizes are needed for most studies. As large dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…For example, in the aspect of syntactic error detection, Ahmed et al (2022) found that SMOSS model can identify local errors in learners' sentences and provide targeted correction suggestions, thus helping learners improve their writing expression [12]. LSTM is a kind of recurrent neural network (RNN), which is designed with memory units, and can better deal with long-term dependence [13]. In the eld of natural language processing, LSTM model performs well in language modelling, machine translation, semantic analysis and other tasks.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, in the aspect of syntactic error detection, Ahmed et al (2022) found that SMOSS model can identify local errors in learners' sentences and provide targeted correction suggestions, thus helping learners improve their writing expression [12]. LSTM is a kind of recurrent neural network (RNN), which is designed with memory units, and can better deal with long-term dependence [13]. In the eld of natural language processing, LSTM model performs well in language modelling, machine translation, semantic analysis and other tasks.…”
Section: Literature Reviewmentioning
confidence: 99%